Depositional Setting of the Jeribe Formation in Selected Subsurface Sections, Northern Iraq - Ibraheem, Muwafaq S.; Kareem , Yaseen S.; Salih, Abdulsalam M. (Iraqi Journal of Science, 2023)
The current research studies the depositional setting of the Jeribe Formation in the south Mosul area of northern Iraq, which is tectonically located in the Low Folded Zone characterized by the deposition of limestone and marly limestone of the Jeribe Formation during the Middle Miocene. Petrography has provided a diversity of fauna such as benthonic foraminifera (Miliolid, Peneroplis sp., Dendritina sp. and Borelis melo curdica) in addition to Red Algae and Mollusca. The Jeribe carbonates were affected by various diagenetic processes such as dolomitization, neomorphism, cementation, anhydritization, compaction and dissolution. Many microfacies have been identified, including lime mudestone, wackestone, packstone and Milioldal grainstone, with eight submicrofacies (Non-Fossiliferous lime mudstone, Benthonic lime mudstone, Fossiliferous wackestone, Red Algal wackestone, Milioldal packstone, Fossiliferous packstone, Green Algal packstone and Red Algal packstone). Depending on microfacies analysis, the Jeribe Formation was deposited in restricted and open marine environments within an interior platform setting.